Students' Perspectives on Innovation of Mathematics Learning Online Course on Their Ability to Develop Innovative Textbooks - Satrio Ardiansyah, Adi; Permata Octalia, Rembulan; Siswandari, Herlina; Rizal, Nur; Fadiarahma Vistara, Maydilla (KnE Social Sciences, 2024)
The responsibility for developing professional and high-quality teacher candidates lies with the Education Institution for Educational Personnel (LPTK). However, achieving this goal is certainly challenging to achieve during this pandemic. This research explores student perspectives on the effectiveness of lectures in developing the ability to create innovative textbooks. The research employed quantitative descriptive methods and involved students from the mathematics education study program Universitas Negeri Semarang who were enrolled in the Innovation of Mathematics Learning course. The data were collected through questionnaires and analyzed using descriptive statistics. The results of the study indicate that preparing learning resources in modules is crucial during lectures. Additionally, activities such as synchronous lecture activities, use of Learning Management System (LMS), resources like videos, discussions with colleagues, virtual face-to-face, discussions using WhatsApp Group, presentation of each assignment, group assignments, and projects should be prepared during lectures. These results highlight the necessity of implementing a team-based project model to develop students’ abilities in developing innovative textbooks. Keywords: innovative textbooks, mathematics learning online course, students’ perspectives.